ANTITHROMBOTIC THERAPY IN ATRIAL FIBRILLATION: NEW DATA AND NEW HORIZONS - M. Yu. Gilyarov; V. A. Sulimov (Столичная издательская компания, 2016)
New data and perspectives of antithrombotic therapy are highlighted in patients with atrial fibrillation. Factors of warfarin therapy efficacy, as well as the possibility of new antithrombotic drugs are considered. Special attention are paid to the direct thrombin inhibitors - dabigatran. Possibilities and usage prospects of dabigatran in patients with atrial fibrillation are discussed in detail in the light of new results of RE-LY trial.